Improving Narrative Production in Children With Language Disorders: An Early-Stage Efficacy Study of a Narrative Intervention Program - Gillam, Sandra L.; Olszewski, Abbie; Squires, Katie; Wolfe, Katie; Slocum, Timothy; Gillam, Ronald B. (Language, speech & hearing services in schools, 2018)
Purpose: As noted in this forum, more research is needed to support the work of school-based speech-language pathologists who are designing and implementing interventions for students with language disorders. This article presents the findings of a multiple-baseline, single-subject study that was conducted to assess the outcomes of an intervention designed to improve narrative discourse proficiency for children with language disorders. Method: Four school-age children with language disorders that included deficits in narration received an experimental version of a 3-phase narrative language intervention program called Supporting Knowledge in Language and Literacy (Gillam, Gillam, & Laing, 2014). Two additional children remained in baseline throughout the study and served as controls for history, testing, and maturation effects. Measures of story productivity (number of different words) and overall story complexity (Monitoring Indicators of Scholarly Language; Gillam, Gillam, Fargo, Olszewski, & Segura, 2016) were used to assess the children's self-generated narratives. Results: After the onset of treatment, all 4 children who received the narrative intervention made moderate-to-large improvements in narrative productivity (number of different words). Three of the 4 children also made moderate-to-large improvements in narrative complexity (Monitoring Indicators of Scholarly Language). The narrative abilities of the 2 children who did not receive intervention did not change over the course of the study. Conclusion: This study provides evidence for the feasibility of the Supporting Knowledge in Language and Literacy narrative instruction program for improving self-generated narratives by children with language disorders. Future research is needed to determine how gains in oral narration transfer to written narrative skills.